MATERNAL AND FETAL OUTCOMES ASSOCIATED WITH RUNNING DURING PREGNANCY: A SYSTEMATIC REVIEW - Nowak, Jan; Szeidl, Olga; Mikołajczyk, Jagoda; Hawajski, Artur; Mielnicka, Weronika; Mieruszyńska, Stella; Sławińska, Julia; Kołodziejska, Maja; Lewandowski, Marcin; Cupiał, Anna (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Running is one of the most popular forms of physical activity among women of reproductive age; however, pregnancy and the postpartum period involve substantial physiological, biomechanical, and psychosocial changes that may affect training continuation and safe return to sport. Body mass gain, a shift in the center of gravity, increased joint laxity, and cardiovascular and respiratory adaptations alter running biomechanics and may influence musculoskeletal load and pelvic floor function.Evidence suggests that physical activity during pregnancy is associated with improved well-being, weight control, and metabolic outcomes, while supervised exercise may enhance mental health and selected cardiometabolic markers. At the same time, appropriate monitoring of exercise intensity and individualized load adjustment remain essential, particularly in competitive athletes.Return to running postpartum should follow a staged, criteria-based approach that considers biopsychosocial factors. Overall, running during pregnancy represents a complex issue requiring interdisciplinary, evidence-based guidance. This systematic review critically synthesizes current literature, highlighting benefits, limitations, and gaps to inform future research and clinical practice.Methods: This review synthesizes recent literature (2015–2026) on running and pregnancy.                   A comprehensive search of PubMed, Scopus, and Google Scholar was conducted using keywords including "running", "pregnancy", "physical activity", "pregnant", "maternity" and "mother well-being". All relevant studies were considered to provide an inclusive overview of current evidence.Aim of The Study: The aim of this perspective review is to synthesize and critically evaluate current research on the effects of running on pregnancy as documented in the recent literature.Conclusion: The literature review indicates that running during pregnancy—when no medical contraindications are present and training loads are appropriately modified—may represent a safe and potentially beneficial form of physical activity. Individual context remains crucial, including pre-pregnancy fitness level, health status, pregnancy course, and the quality of medical and physiotherapeutic support.Current evidence suggests that moderate running may support weight control, metabolic profile, and cardiorespiratory fitness without increasing the risk of preterm birth in healthy women. However, the high prevalence of musculoskeletal complaints and the potential risk of pelvic floor dysfunction highlight the need for functional assessment and targeted stabilization training.Postpartum return to running should follow a staged, criteria-based approach rather than a purely time-based model. Although existing evidence is heterogeneous and largely observational, individualized, evidence-based recommendations and interdisciplinary care appear essential for safe and effective practice.